Family relationships and LGB first homelessness in Australia: What do we know and where should we go?. (December 2020) - Dempsey, Deborah; Parkinson, Sharon; Andrews, Cal; McNair, Ruth
Family conflict is a well-documented causal factor in the international literature on youth homelessness. Less is known about how childhood experiences within family of origin contribute to first homelessness among Australian lesbian, gay, bisexual, transgender and queer (LGBTQ+) young people. In this article, which draws on an analysis of the Australian Journeys Home survey, we argue that homelessness risk among LGB young people is cumulative and stems from multiple childhood disadvantages. LGB respondents were more likely than their heterosexual peers to report leaving home in the early teens. They were also more likely to have experienced conflict, abuse and deprivation in their families of origin, including: the threat of harm from someone within the family home environment; a lack of adequate food and shelter during childhood; high levels of childhood sexual abuse; and early experience of parental divorce. We discuss the implications of these findings for future LGBTQ+ research agendas.